An Implementation Approach to Rotation Programs - Ville Korpela; Michele Lombardi; Riccardo D. Saulle (Fondazione Eni Enrico Mattei (FEEM), 2021)
Rotation programs are widely used in societies. Some examples are job rotations, rotation schemes in the management of common-pool resources, and rotation procedures in fair division problems. We study rotation programs via the implementation of Pareto efficient social choice rules under complete information. The notion of the rotation program predicts the outcomes. A rotation program is a myopic stable set whose states are arranged circularly, and agents can effectively move only between two consecutive states. We provide characterizing conditions for the implementation in rotation programs and show that, for multi-valued rules, our notion of rotation monotonicity is necessary and sufficient for implementation. Finally, we identify two classes of assignment problems that are implementable in rotation programs.
Keywords: C71; D71; D82; 330; Rotation Programs; Job Rotation; Assignment Problems; Implementation; Right Structures; Stability